STUDY OF THE EFFECT OF "VES ANTI CREASE SB-38" BASED APPRET IN THE CHEMICAL FINISHING PROCESS OF COTTON-NITRON FIBER TEXTILE MATERIALS - Khasanova Makhfuza Shukhratovna (Web of Journals Publishing, 2024)
By treating fabrics with various chemicals under certain conditions, their properties and qualities are changed according to the purpose. Blended fabrics are produced primarily using chemical fibers and threads, the share of which in the total volume of raw materials processed by the textile industry is over 97%, about 3% is natural fibers: silk, cotton and wool, which are used for the production of dress, haberdashery, lining and shirt fabrics. As a result of finishing, yarn yarns will not have the property of being completely wrinkle-free. Therefore, it is desirable to give them the property of low shrinkage. Mixed fiber fabrics containing hydrocellulose and cellulose fibers have sufficient plastic deformation properties. Such mixed fabrics wrinkle quickly. In the final finishing processes, blends of fabrics containing natural and man-made fibers were treated with a sizing compound using Ves Anti Crease SB-38 to achieve a low-crease, low-shrink finish. The effect of finishing agents concentration on the color characteristics of mixed fabrics was studied.
Keywords: Mixed fiber fabric, cotton-nitron, low permeability, low shrinkage, total opening angle, appret, dyeing.